Efficacy and safety of dupilumab for the treatment of moderate-to-severe atopic dermatitis in adults: A pooled analysis of two phase 2 clinical trials. Issue 9 (September 2018) - Tofte, Susan J.; Papp, Kim; Sadick, Neil; Bohnert, Krista; Simpson, Eric; Thaçi, Diamant; Bieber, Thomas; Blauvelt, Andrew; Sofen, Howard; Gooderham, Melinda; Chen, Zhen; Gadkari, Abhijit; et al.
ABSTRACT: Background and purpose: There is a need for new treatment options for moderate-to-severe atopic dermatitis (AD) in adults. Dupilumab, a fully human anti-interleukin-4 receptor α monoclonal antibody, has recently been approved for this indication. Methods: A pooled analysis of a phase 2a (NCT01548404) and a phase 2b (NCT01859988) study and a subanalysis of the 2b study evaluated the efficacy and safety of subcutaneous dupilumab 300 mg once weekly (qw) and every 2 weeks (q2w) in adults with moderate-to-severe AD. Results: Dupilumab significantly improved clinical outcomes in both analyses at week 12. Itch was significantly improved in the pooled analysis as measured by peak pruritus Numerical Rating Scale, 5-dimension pruritus scale, and SCORing Atopic Dermatitis (SCORAD) Visual Analog Scale (VAS) pruritus scores (all p < .0001 vs. placebo at week 12). Sleep loss was significantly improved (SCORAD VAS sleep loss score; p < .0001 vs. placebo at week 12); similar results were shown for the q2w dose. Dupilumab had an acceptable safety profile. Conclusions: Consistent with previous studies, dupilumab qw and q2w significantly improved signs and symptoms of AD at week 12, including improvements in itch and sleep loss. Implications for practice: Subcutaneous dupilumab is an effective new treatment option for adults with moderate-to-severe AD.